An Analysis of the Reliability of the FASB Data Bank of Changing Price and Pension Information. - Stone, Mary; Bublitz, Bruce (The Accounting Review, 1984)
Abstract ABSTRACT: The FASB has issued computer data tapes for both pension disclosures and inflation-adjusted amounts. This note reports the results of a comparison of a sample of data from the FASB data tapes with amounts from the annual reports. This study warns future users of the tapes of potential pitfalls in their use. All errors have been reported to the FASB for their use in updating the tapes.